2020
DOI: 10.12688/f1000research.22907.1
|View full text |Cite
|
Sign up to set email alerts
|

RamaNet: Computational de novo helical protein backbone design using a long short-term memory generative adversarial neural network

Abstract: The ability to perform de novo protein design will allow researchers to expand the variety of available proteins. By designing synthetic structures computationally, they can utilise more structures than those available in the Protein Data Bank, design structures that are not found in nature, or direct the design of proteins to acquire a specific desired structure. While some researchers attempt to design proteins from first physical and thermodynamic principals, we decided to at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…There are several studies for de novo peptide and protein design in drug design and discovery using GAN-based approaches, including the LSTM-GAN (Long Short-Term Memory Generative Adversarial Network) structure in peptide design [91], the gcWGAN (Guided Conditional Wasserstein Generative Adversarial Network) structure in peptide folding [92], the DCGAN (Deep Convolutional Generative Adversarial Network) structure in protein backbone design [93], the DCGAN structure in target-specific compounds for cannabinoid receptors [94], the GANDALF (Generative Adversarial Network Drug-tArget Ligand Fructifier) structure in peptide design [95], and the Feedback-GAN structure in antimicrobial peptides [96].…”
Section: De Novo Peptide and Protein Designmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies for de novo peptide and protein design in drug design and discovery using GAN-based approaches, including the LSTM-GAN (Long Short-Term Memory Generative Adversarial Network) structure in peptide design [91], the gcWGAN (Guided Conditional Wasserstein Generative Adversarial Network) structure in peptide folding [92], the DCGAN (Deep Convolutional Generative Adversarial Network) structure in protein backbone design [93], the DCGAN structure in target-specific compounds for cannabinoid receptors [94], the GANDALF (Generative Adversarial Network Drug-tArget Ligand Fructifier) structure in peptide design [95], and the Feedback-GAN structure in antimicrobial peptides [96].…”
Section: De Novo Peptide and Protein Designmentioning
confidence: 99%
“…For example, Sabban and Markovsky [91] suggested that the LSTM-GAN structure, a combination method involving the GAN architecture and long short-term memory units, was able to generate novel helical protein backbone topologies with preferred features in the context of de novo protein design. The LSTM-GAN structure employed a long short-term memory unit in the generative network module and another one in the discriminative network module, where the long short-term memory unit is often utilized in the field of natural language processing [97].…”
Section: De Novo Peptide and Protein Designmentioning
confidence: 99%
“…While it remains more challenging to directly generate a distribution of tertiary structures via generative models, notable efforts have been made [11,22,23,27]. Work in [11] does not provide an end-to-end NN-based framework for PSP, but composes a neural energy function with a Langevin dynamics-based simulator and is able to predict more than one type of structure for a given protein sequence.…”
Section: Related Workmentioning
confidence: 99%
“…Work in [11] does not provide an end-to-end NN-based framework for PSP, but composes a neural energy function with a Langevin dynamics-based simulator and is able to predict more than one type of structure for a given protein sequence. A body of recent works [22,23,27] represent the state-ofthe-art on generative NN-based frameworks for problems related to PSP. However, these methods, based on the generative adversarial network (GAN) framework, generate structural fragments of an a-priori determined length (32, 64, or 128) that do not in themselves constitute tertiary structures of a given amino-acid sequence.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to these two generative models, a number of groups have also developed generative models for various purposes in protein design and engineering. [44][45][46][47] Recently, Zhang and coworkers proposed a convolutional neural network for protein sequence design and reached a state-of-the-art accuracy of 42.2% on a test set that shared less than 30% sequence identity with the training set. 48 In this study, we aim to further improve the accuracy of CPD using deep-learning methods.…”
Section: Introductionmentioning
confidence: 99%